SOCIO-CULTURAL LIFE OF UZBEKISTAN IN THE POST-WORLD WAR II - Tashkentboy Rajabovich Pardaev (Scholar Express Journal, 2021)
This article analyzes the changes in the cultural life of Uzbekistan in the postwar years of reconstruction, the mistakes and shortcomings, the pressure of the center's great state policy on the cultural life of the republic.
Keywords: Culture; literature; art; theater